COMPARISON OF DIFFERENT HYDRODYNAMIC CHARACTERISTICS OF AIR- WATER SYSTEM USING DISSIMILAR MOTIONLESS MIXERS - Dr. Mazhar Hussain (Sir Syed University Research Journal of Engineering and Technology, 2021)
The hydrodynamic characteristics of mixing fluids are always the points to consider in improvement of their mixing quality especially using motionless mixers normally stated as “Static Mixers”. Motionless mixing technique was adopted for Air-Water system with the advantage of negligible power consumption over dynamic mixers. Different hydrodynamic characteristics were experimented using “Baffle Type” static element and were compared to those of already used in recent studies. Dissolved oxygen content, Static mixer geometry (i.e. Baffle, Blade, Wheel, Plate and Needle), mixing fluids flow rates were chosen as variables and selected in this content as rate of mass transfer study which founds out to be significant using “Baffle Type” static element. Volumetric mass transfer was also achieved at higher scale which gives a clear indication of increase the mass transfer coefficient in between the comparison of “Baffle type” element and other mentioned elements. Pressure droplet and depletion in Air bubble size across static elements were visually perceived using Hg-Manometer and still photography respectively. A mathematical model was also developed portraying the Air bubble diameter at different flow rates for this system. Other hydrodynamics like higher Dissolved Oxygen (DO) Content, Less Power consumption were also found to be more advantageous for “Baffle Type” static element.